Pembelajaran Sains Tentang Penanaman Konsep Benda Terapung, Tenggelam Dan Melayang Pada Kelompok B Ra Al Munawwaroh Ponorogo - Nurtina Irsad Rusdiani; Betty Yulia Wulansari (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2023)
The introduction of science learning is very important for us, especially in early childhood. Science learning for early childhood prioritizes process rather than results. By getting science learning children can think concretely and systematically, with science children can understand the concept of cause and effect that occurs in the surrounding environment both the natural environment or the social environment, children can expand their knowledge, can facilitate children's desires, increase children's interest in study the natural surroundings and provide provisions for the life to come. This study used a descriptive qualitative method, conducted at RA AL Munawwaroh Ponorogo. From the results of the research conducted, it was found that science learning must use experimental activities so that children can see and pay attention directly to the changes that occur in the learning. Items used for science learning must be concrete objects that are easy for children to find in their environment. Planting science concepts, one of which is sinking, floating and floating objects in early childhood. A floating object is an object in a state of equilibrium and is affected by the action of two forces, namely the weight of the object and the buoyant force, which is equal to the weight of the liquid. Mattress is when the volume of the liquid is equal to the volume of the object. An object sinks when the mass of the object is greater than the density of the liquid.